Mental health trajectories from adolescence to adulthood: Language disorder and other childhood and adolescent risk factors. (27th November 2015) - Bao, Lin; Brownlie, E. B.; Beitchman, Joseph H.
Abstract: Longitudinal research on mental health development beyond adolescence among nonclinical populations is lacking. This study reports on psychiatric disorder trajectories from late adolescence to young adulthood in relation to childhood and adolescent risk factors. Participants were recruited for a prospective longitudinal study tracing a community sample of 5-year-old children with communication disorders and a matched control cohort to age 31. Psychiatric disorders were measured at ages 19, 25, and 31. Known predictors of psychopathology and two school-related factors specifically associated with language disorder (LD) were measured by self-reports and semistructured interviews. The LD cohort was uniquely characterized by a significantly decreasing disorder trajectory in early adulthood. Special education was associated with differential disorder trajectories between LD and control cohorts, whereas maltreatment history, specific learning disorder, family structure, and maternal psychological distress were associated with consistent trajectories between cohorts. From late adolescence to young adulthood, childhood LD was characterized by a developmentally limited course of psychiatric disorder; maltreatment was consistently characterized by an elevated risk of psychiatric disorder regardless of LD history, whereas special education was associated with significantly decreasing risk of psychiatric disorder only in the presence of LD.